2016
DOI: 10.1038/srep37385
|View full text |Cite
|
Sign up to set email alerts
|

Giant frequency down-conversion of the dancing acoustic bubble

Abstract: We have demonstrated experimentally the existence of a giant frequency down-conversion of the translational oscillatory motion of individual submillimeter acoustic bubbles in water in the presence of a high frequency (500 kHz) ultrasonic standing wave. The frequency of the translational oscillations (~170 Hz) is more than three orders of magnitude smaller than that of the driving acoustic wave. We elucidate the mechanism of this very slow oscillation with an analytical model leading to an equation of translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, a theoretical insight can be gained from the analysis of a system consisting of just two moving gas bubbles 52 , where it has been shown that stronger ultrasound forcing prevents bubble collision and coalescence thereby increasing the stability of their oscillations. On the other hand, similar to a single oscillating bubble [54][55][56][57][58] , the translational motion in bubble clusters should depend www.nature.com/scientificreports/ on the frequency and pressure of the driving wave. Thus, it is plausible to assume that driving the bubble cluster at a higher frequency but lower pressure, which is the case in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, a theoretical insight can be gained from the analysis of a system consisting of just two moving gas bubbles 52 , where it has been shown that stronger ultrasound forcing prevents bubble collision and coalescence thereby increasing the stability of their oscillations. On the other hand, similar to a single oscillating bubble [54][55][56][57][58] , the translational motion in bubble clusters should depend www.nature.com/scientificreports/ on the frequency and pressure of the driving wave. Thus, it is plausible to assume that driving the bubble cluster at a higher frequency but lower pressure, which is the case in Fig.…”
Section: Resultsmentioning
confidence: 99%